Decolourization of Acid Red 131 by using Shigella sp Isolated from Tannery Effluent - Sivaranjani, A (International Journal of Pharmaceutical & Biological Archive, 2013)
Decolourization of Acid Red 131 by using Shigella sp Isolated from Tannery Effluent